Pengaruh Ukuran Perusahaan, Profitabilitas Dan Likuiditas Terhadap Kebijakan Dividen Pada Perusahaan Sub Sektor Food and Beverage yang Terdaftar Di Bursa Efek Indonesia Periode 2021-2022 - Hendri Mauliansyah; Elviza (BE-HISZ : Journal of Economics and Accounting, 2024)
This study aims to determine the effect of Company Size, Profitability, and Liquidity on  Dividend Policy in Food and Beverage Sub-Sector companies listed on the Indonesia Stock Exchange for the period 2021-2022. The type of research is quantitative method. The observation population in this study consists of 40 samples of financial statements from Food and Beverage Sub Sector companies listed on the Indonesia Stock Exchange for the period 2021-2022. The object of this research is the companies in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange. The data analysis technique in this study uses multiple linear regression analysis. The type of data used in this research is secondary data. The research results show that Company Size, Profitability, and Liquidity have a positive effect on Dividend Policy in companies in the Food and Beverage Sub-Sector listed on the Indonesia Stock Exchange for the period 2021-2022, both simultaneously and partially.